PENINGKATAN KEMAMPUAN PEGAWAI PERPUSTAKAAN DALAM MELAKSANAKAN PELAYANAN TEKNIS MELALUI MODEL PEMBINAAN CLCK (CONTOH, LATIHAN, CONTROL, KERJA MANDIRI) DISMAN 2 LUHAK NAN - Kusuma Winanto (STKIP Pesisir Selatan, 2020)
Based on observations and supervision conducted by the author, it shows that library staff at SMAN 2 Luhak Nan Duo do not have good skills and abilities in library management activities especially in terms of technical services. The purpose of this study was to describe and obtain information about efforts to improve the ability of library staff in carrying out technical services through the CLCK development model (Example, Training, Control, Independent Work) at SMAN 2 Luhak Nan Duo.This research is a school action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 2 library employees at SMAN 2 Luhak Nan Duo. Research data were collected using observation sheets. Data were analyzed using averages.The results showed that the implementation of CLCK training (Example, Exercise, Control, Independent Work) could improve the ability of teachers to carry out technical services. This is evidenced based on preliminary data on the ability of employees before the implementation of the CLCK program, the average ability of employees is still in the poor category. Then after developing the CLCK model, the ability of employees increased to 79.28 (good) in the first cycle and after that increased in the second cycle to 88.7 (very good).